The Effect Of Physical Fatigue On Football Referee's Decision Making - Yudi Nurcahya; Agus Rusdiana; Yusuf Hidayat; Dikdik Zafar Sidik; Widi Kusumah; Moch Yamin; Fauzan Nur Akbar (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2023)
The role of the referee is very important, especially in professional football. Wrong decisions may have a profound impact on the outcome of the match. Research is needed to find out the aspects that influence referee decisions. This research aims to determine the effect of fatigue experienced by referees on decision making. This research used an experimental method with 16 football referees as the sample. The research instrument was a video test of soccer referee decision-making from UEFA 2022. The results of this research show a significant influence of fatigue experienced by referees on decision-making. Fatigue experienced by referees interferes with referees in making decisions